Bad for Girls and Boys: Gender Does Not Modify the Negative Effect of Physical Inactivity on Life Satisfaction in Adolescents - Lábiscsák-Erdélyi, Zsuzsa; Somhegyi, Annamária; Veres-Balajti, Ilona; Kósa, Karolina (Frontiers in Public Health, 2022)
Objectives: Physical activity (PA) has positive effect on life satisfaction (LS) among adolescents but the moderating effect of gender and level of PA intensity have been equivocal. Our aim was to examine the pattern of physical activity by grade in high school students, and the role of gender and grade on the association between physical activity and life satisfaction. Methods: Four repeated cross-sectional online questionnaire surveys between 2011-2013 were carried out among all students in one Hungarian high school (N=3450). Health status and behaviour was assessed by the Hungarian online version of the Health Behaviour of School-aged Children (HBSC) questionnaire. Regression with robust variance estimator was used to identify determinants of life satisfaction. Results: Good self-reported health as opposed to bad increased life satisfaction by 0.30 standard deviation; having very well or well-off family as opposed to not well-off increased LS by 0.16 standard deviation; and being inactive compared to being vigorously active decreased LS by 0.1 standard deviation. Conclusions: Physical inactivity has a negative effect on life satisfaction in boys and girls regardless of grade but compounded by low perceived family wealth.